2023
DOI: 10.1111/apa.16735
|View full text |Cite
|
Sign up to set email alerts
|

NICU parents' mental health: A comparative study with parents of term and healthy infants

Abstract: Parents of infants in need of neonatal care are often not mentally prepared for the experience; they become parents to a sick or preterm infant in a scary and unfamiliar place where they face surreal, chaotic and deeply distressing situations. 1 Most parents in neonatal intensive care units (NICUs) exhibit depressive symptoms or symptoms of psychological trauma. A stressful birth experience, uncertain outcome or uncertain survival of the infant, early and prolonged separation and unclear responsibilities for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Unfortunately, for those who traverse the NICU, the experience is quite traumatic 16,17 and the emotional impact on the parents has been well documented. [18][19][20][21] In a unique article by Janvier et al, 18 neonatologists who themselves had offspring that spent an extended period in the NICU recognized This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, for those who traverse the NICU, the experience is quite traumatic 16,17 and the emotional impact on the parents has been well documented. [18][19][20][21] In a unique article by Janvier et al, 18 neonatologists who themselves had offspring that spent an extended period in the NICU recognized This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, for those who traverse the NICU, the experience is quite traumatic 16,17 and the emotional impact on the parents has been well-documented. [18][19][20][21] In a unique article by Janvier et al, 18 neonatologists who themselves had offspring that spent an extended period in the NICU recognized the psychological toll of having a child in the unit on parents. Noting the impact the experience had on them, they described a shift in their understanding of the effect of staying in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…These include infections, hypertension, increased postpartum bleeding, generalized infections, and genital tract infections. It has been demonstrated that patients who give birth before completing 37 weeks of gestation require longer hospitalization and rehabilitation [ 70 , 71 , 72 , 73 ].…”
Section: Influence Of Prematurity On the Mother And Familymentioning
confidence: 99%
“…PTG can also guide parents to cherish life more deeply, adopt healthier coping strategies, and utilize available social resources to address problems, thereby improving the quality of care they provide to their children [7]. A previous study has reported that parents of VLBW newborns experience signi cant psychological distress in the months following birth, with higher levels of mental health issues, increased parenting stress, and negative impacts on family dynamics compared to parents of fullterm, normal birth weight children [10,11]. Focusing on PTG levels during the hospitalization of VLBW infants is crucial for enhancing parental care quality and alleviating their stress.…”
Section: Introductionmentioning
confidence: 99%